Fifteen-minute consultation: perinatal palliative care. Issue 3 (14th November 2016) - Sidgwick, Peter; Harrop, Emily; Kelly, Brenda; Todorovic, Ana; Wilkinson, Dominic
Abstract : Perinatal palliative medicine is an emerging subspecialty within paediatric palliative medicine, neonatal medicine, fetal medicine and obstetrics. It comprises patient-focused, non-judgemental shared decision making and aims to provide holistic multidisciplinary support for families. In this paper we define and describe one model for providing perinatal palliative care, drawing on the personal and professional experience of the authors.